Addiction among Health Care Professionals? What is the Current State of Nurses, Caregivers and Paramedics in 2022? A Review - Amirouche, Ammar; Felix, Hugo; Serreau, Raphaël; Denormandie, Philippe; Fernandez, Julia; Coscas, Sarah; Blecha, Lisa; Benyamina, Amine (Archives of Clinical and Biomedical Research, 2023)
Background: The COVID-19 pandemic has had a significant impact on organizations, health care professionals and of course patient care. The ability of health care facilities and their personnel to deliver safe, quality care was tested under particularly stressful conditions over the past two years. Health care workers represent a vulnerable population, especially during periods of high demand such as a major pandemic. This may in turn be associated with an increased risk of alcohol and substance use, abuse and disorders. There exists a correlation between psychotropic drug use and ensuing job difficulties increasing professional and emotional exhaustion among health care professionals. Aims and Objectives: To describe the current state of nurses, caregivers and paramedics in terms of substance use, mental health and burnout after two years of the COVID-19 pandemic in France. Design: Level exploration of health care professionals’ addiction and burnout in France with PRISMA check-list. Method: Review of the literature in Pubmed, Scholar, social data and website until October 15, 2022. Results: Drug and alcohol misuse among healthcare workers is estimated to be between 10 and 15%. It has increased since the COVID-19 pandemic. Psychoactive substance misuse such as excessive alcohol consumption can lead to decreased efficacy and cognitive performance in the days following its use. Nurses may also be at an increased risk of opioid and benzodiazepine misuse compared to other populations of healthcare workers. Conclusions: We need to examine the current situation concerning addictions and burnout among all healthcare professionals in France and around the world in order to determine optimal care management. Relevance to Clinical Practice: This is a necessary step in order to improve screening and diagnosis of psychological distress among healthcare professionals in France particularly nurses, caregivers and paramedics.